KEBIJAKAN KRIMINALISASI DALAM REFORMASI HUKUM KELUARGA DI INDONESIA - Barkah, Qodariah (Nurani, 2017)
The family law reform policy has been started since 1937 the Dutch colonial government drafted a modern marriage bill called the Marital Recording Ordinance. This step was taken at the urging of the existing women's organizations, and then the international community made efforts to reform family law since the 1970s, known as the UN women's convention. So human equality is seen as essential for justice, but this leaves plenty of room for different views on the fairest way to accommodate differences. However, family law reform efforts, especially in Indonesia continue to roll from 1974 until now.